The Effect of Regional Revenue on Economic Growth with Capital Expenditure as Mediation Variable – A Case of North Sumatera Province - Octreshia Ellendythia Marpaung (Proceedings of AICS - Social Sciences, 2017)
This study aimed to analyze the effect of capital expenditure in mediating the relationship between Regional Generated Revenues (PAD), General Allocation Fund (DAU), Specific Allocation Fund (DAK), and the Revenue Sharing Fund (DBH) to the economic growth as measured by the Regional Gross Domestic Product (PDRB) in North Sumatera Province. The data used are secondary data obtained from the Central Statistical Agency (BPS) and the site of Directorate General of Fiscal Balance (www.djpk.depkeu.go.id) of North Sumatra Province for the period of 2010 to 2015. This research is quantitative descriptive with multiple regression analysis method. The results of the research showed that simultaneously PAD, DAU, DAK, and DBH had positive and significant effect on economic growth